Association of fatty acid desaturase 2 gene polymorphism (rs28456) with susceptibility to bipolar disorder in the Turkish population: a case-control study - Pirim, Dilek; Gümüş, Ceren; Boztepe, Esra; Akdağ, Emine Merve; Şirin, Hande (Archives of Biological Sciences, 2024)
Paper description: Variations in the genes related to fatty acid metabolism may contribute to the risk of bipolar disorder (BD). The dysregulation of fatty acid desaturase 2 (FADS2) in BD patients indicates that it may be involved in BD development. Limited population-specific research suggests a potential association between the regulatory gene variant rs28456 in FADS2 and BD. FADS2 rs28456 may be associated with BD in a gender-specific manner and could potentially play a role in BD development as a non-modifiable risk factor. Abstract: The FADS2 gene encodes a key, rate-limiting enzyme involved in polyunsaturated fatty acid (PUFA) metabolism. Recent studies suggest that changes in plasma PUFA levels can lead to disruptions in the neurotransmission system and increase the risk of mood disorders. FADS2 variations may contribute to the individual risk of developing bipolar disorder (BD). We investigated the association of regulatory FADS2 rs28456 with BD in the Turkish population. We performed TaqMan genotyping on 100 patients with BD and 91 healthy controls. Our results did not show significantly different genotype or allele frequencies of rs28456 in the BD cases compared to controls. However, we stratified the cases based on family history, which revealed that minor rs28456-G was observed more frequently (P=0.056) in cases without a family history of psychiatric illness compared to those with a family history of psychiatric illness. A marginally significant difference in the distribution of the “G” allele (P=0.053) between male patients and healthy males without a family history was observed. Our findings did not provide strong evidence supporting the reported association between rs28456 and BD, yet they point to its potential gender-specific effect, which requires further investigation. Future studies are necessary to explore the impact of FADS2 variations on BD risk in larger study groups, considering their potential interaction with non-inherited risk factors.